Inclusive higher education: debates and contemporary trends in Latin America - Ramírez Narváez, Javier (2022)
This article is a theoretical review that aimed to identify contemporary debates and trends around higher education in Latin America. For this purpose, the available information contained in specialized databases (Scopus, Scielo and Dialnet) related to inclusive higher education in Chile, Colombia, Ecuador, Mexico and Peru was consulted; during the years 2017 and 2022. As a result, it was possible to know that the research carried out in this period revolved around three problems, whose questions by the authors led them to investigate from pedagogy, law and sociology mainly, focusing with more impetus in the field of action towards disability, inclusion and social equity; preferring to a greater extent the use of the qualitative approach. It is concluded that, for the existence of inclusion within higher education in Latin America, it must be appreciated and recognized as a right of all people, keeping in mind that diversity emerges in each of them.